2021
DOI: 10.3389/fnut.2021.714291
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Dairy Product Consumption and Asthenozoospermia Risk: A Hospital-Based Case-Control Study

Abstract: Background: Evidence of an association between dairy product and main related dairy nutrient intake, and the asthenozoospermia risk have been limited and controversial.Methods: A hospital-based case-control study including 549 men with asthenozoospermia and 581 normozoospermic controls was carried out in the infertility clinics of Shengjing Hospital of China Medical University between June, 2020 and December, 2020. Dietary intake was assessed with a validated food frequency questionnaire. According to the Worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The AHEI-2010 and DASH scores were characterized by high intakes of fruit, vegetables, whole grains, and legumes and low intakes of sugar-sweetened, red/processed meat, and sodium. These high intake food groups were found to be positively associated with sperm count ( 3 , 19 ), concentration ( 19 ), sperm motility ( 20 , 21 ), and morphology ( 3 , 19 ). These food groups serve as major sources of vitamins, minerals, and polyphenols, which are be considered antioxidant and anti-inflammatory.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The AHEI-2010 and DASH scores were characterized by high intakes of fruit, vegetables, whole grains, and legumes and low intakes of sugar-sweetened, red/processed meat, and sodium. These high intake food groups were found to be positively associated with sperm count ( 3 , 19 ), concentration ( 19 ), sperm motility ( 20 , 21 ), and morphology ( 3 , 19 ). These food groups serve as major sources of vitamins, minerals, and polyphenols, which are be considered antioxidant and anti-inflammatory.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, these two dietary scores recommend reduction in sugar-sweetened beverage, red/processed meat, and fat consumption. The relatively high content of sugars, saturated/trans fatty acids, and sodium may adversely affect sperm count ( 19 ), concentration ( 29 , 30 ), sperm motility ( 3 , 20 ), and morphology ( 3 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study followed the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist ( Supplemental Table 1 ). The details of the study design and participants have been described in previously published studies ( 3 , 11 ). Briefly, a hospital-based case-control study was performed at Shengjing Hospital of China Medical University, in Liaoning, China.…”
Section: Methodsmentioning
confidence: 99%
“…As one of the most important environmental factors, the diet factor has also been proposed to play crucial roles in the etiology of asthenozoospermiais ( 10 , 11 ). Ultra-processed foods (UPFs) are formulations of ingredients, mostly of exclusive industrial use, that result from a sequence of industrial processes ( 12 ), and they have been indicated to have many adverse effects on human health ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%